Annual Report 2007-08 - Planning Commission (Planning Commission, 2007)
The Planning Commission was constituted in March, 1950 by a Resolution of the Government of India, and it works under the overall guidance of the National Development Council. The Planning Commission consults the Central Ministries and the State Governments while formulating Five Year Plans and Annual Plans and also oversees their implementation. The Commission also functions as an advisory Planning body at the apex level.
Government of India Planning Commision New Delhi
Keywords: Agriculture Division; Backward Classes; SC and Tribal Development; Bharat Nirman Programme; Communication & Information Division; Development Policy Division; Education Division; Economic Advisory Council to the Prime Minister; National Knowledge Commission; Environment & Forests Division; Financial Resources Division